2018
DOI: 10.1021/acs.nanolett.8b02229
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Targeted against Cryptococcal Pneumonia by Interactions between Chitosan and Its Peptide Ligand

Abstract: Inspired by the fact that chitosan is a representative constituent of the ectocellular structure of Cryptococcus neoformans and a typical biomaterial for improving drug oral absorption, we designed an elegant and efficient C. neoformanstargeted drug delivery system via oral administration. A chitosan-binding peptide screened by phage display was used as the targeting moiety, followed by conjugation to the surface of poly(lactic-co-glycolic acid) nanoparticles as the drug carrier, which was then incubated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 37 publications
0
41
0
1
Order By: Relevance
“…The prepared nanodrug can be administered orally and has targeting property. The results showed that the nanodrug could significantly kill Cryptococcus neoformans in lung infection foci, thus improving the survival rate of infected mice [178]. Studies have shown that biodegradable ITZ-loaded d-a-tocopheryl PEG 1000 succinate-b-poly(e-caprolactoneran-glycolide) NPs (designed as ITZ-loaded tripolyphosphate (TPP) NPs) can improve the antifungal efficacy.…”
Section: Fungus Infectionsmentioning
confidence: 99%
“…The prepared nanodrug can be administered orally and has targeting property. The results showed that the nanodrug could significantly kill Cryptococcus neoformans in lung infection foci, thus improving the survival rate of infected mice [178]. Studies have shown that biodegradable ITZ-loaded d-a-tocopheryl PEG 1000 succinate-b-poly(e-caprolactoneran-glycolide) NPs (designed as ITZ-loaded tripolyphosphate (TPP) NPs) can improve the antifungal efficacy.…”
Section: Fungus Infectionsmentioning
confidence: 99%
“…Targeted delivery at the disease site is currently of great interest in the biomedical field. From the recent works on biosensors, Surface Plasmon Resonance (SPR) has been widely used to monitor the biomolecular interactions that can detect the interaction between functionalized nanoparticles with a specific ligand [ 35 , 36 ]. To investigate the binding affinity between A10-PBM-NP and PSMA, we employed covalent coupling on sensor ship-based SPR.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, free chitosan (C-CP-NPs/ITZ) did not influence the efficiency of drug incorporation and it did not impact drug release. Both CP-NPs/ITZ and C-CP-NPs/ITZ prolonged the survival of mice with pulmonary cryptococcosis, although C-CP-NPs/ITZ was more effective (Tang et al, 2018 ).…”
Section: Current Scenario Of Nanotechnology In the Treatment And Vaccmentioning
confidence: 99%